Metalimnobia crane flies (Diptera: Limoniidae) from Korea - Podenas, Sigitas; Byun, Hye-Woo (Zootaxa, 2016)
Korean species of the crane fly genus Metalimnobia Matsumura, 1911 (Diptera: Limoniidae), are taxonomically revised. Metalimnobia (Metalimnobia) channpayna new species, is described and figured, M. (M.) bifasciata (Schrank, 1781), M. (M.) quadrinotata (Meigen, 1818) and M. (M.) zetterstedti (Tjeder, 1968) are listed for the first time in Korea, new information for previously known species, M. (M.) quadrimaculata (Linnaeus, 1760) is added. Identification key for all Korean Metalimnobia species is given. Wings, male and female terminalia are illustrated for all species.